Musical Minhag: Negotiating Prayer Melodies in a Liberal Synagogue in Vienna - Isabel Frey (Musicologica Austriaca, 2024)
This article examines the negotiation of prayer melodies at Or Chadasch, a liberal Jewish synagogue in Vienna, exploring how these melodies represent the community’s balance between tradition and innovation within a progressive Jewish framework. As a “minority within a minority,” Or Chadasch operates on the periphery of Vienna’s Orthodox-dominated Jewish community and global progressive Judaism. The article begins by providing a historical context for progressive Judaism in Austria and by tracing the development of Or Chadasch and its repertoire of prayer melodies. Drawing on ethnographic fieldwork, it explores how the emotional connections of congregants and prayer leaders to specific melodies shape debates on musical tradition, continuity, and communal belonging. Central to this analysis is the concept of minhag (custom), an insider term that serves as a flexible yet deeply rooted foundation in the musical worship practices of the congregation. The article identifies six “modes of minhag”—continuity, habit, authority, potluck, participation, and choice—as distinct approaches through which congregants negotiate persistence and change in prayer melodies. These modes illustrate how minhag functions as both a stabilizing and adaptive force, which accommodates diverse attachments across transnational and transhistorical Jewish musical practices. The study posits that minhag, understood as enacted through multiple modes, transcends a simple binary of tradition versus innovation. Furthermore, the article situates the musical minhag of Or Chadasch within broader ethnomusicological research on minority communities, arguing that this minhag reflects the specific historical, ideological, and sociopolitical positioning of the congregation, thus serving as a living archive of the community’s history.